Health care and poor relief in Portugal. An historical perspective - Abreu, Laurinda (2020)
This contribution has two main objectives. First, it seeks to describe the policies that governed the provision, regulation and distribution of poor-relief and healthcare resources in Portugal in the sixteenth to eighteenth centuries. Secondly, it attempts to account for the persistence of the poor-relief system established at the turn of the sixteenth century, together with its financial underpinning. The main features of this system are discussed on the basis of its primary components – hospitals, misericórdias (charitable institutions) and officially accredited health professionals. This article draws on previously published works (especially Abreu, 2018a, 2018b, 2018c), where the reader will find further details and references.